2023
DOI: 10.1111/1365-2435.14343
|View full text |Cite
|
Sign up to set email alerts
|

Effects of long‐term mowing on leaf‐ and root‐associated bacterial community structures are linked to functional traits in 11 plant species from a temperate steppe

Abstract: Long‐term mowing can cause morphological stuntedness of plants, thus reducing grassland productivity and exacerbating grassland degradation. Although plant microbiomes can enhance plant resistance against disturbance, considerable uncertainty exists regarding how mowing and mowing‐induced plant trait plasticity affect plant microbiomes in natural grasslands. Here we examined the responses of leaf/root‐associated bacterial (LAB/RAB) communities of 11 dominant herbaceous perennials (six replicates per species) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…Relocation as a strategy to avoid environmental changes might often fail because of time constraints, continued habitat shrinking, or a lacking spatial connectivity within a species’ range of dispersal (Asamoah et al, 2021; Corlett & Westcott, 2013; Gómez-Ruiz & Lacher Jr, 2019; Renton et al, 2013); likewise, the process of evolutionary adaptation to rapid alterations also takes several generations and might be too slow in most cases (Etterson & Shaw, 2001). Our data experimentally support recent findings that land-use not only affects plants and plant communities, but also the diversity and composition of plant-associated bacterial and fungal communities (Bai et al, 2023; Estendorfer et al, 2017; Gaube et al, 2021). Our data additionally demonstrate the pace and small scale of such alterations: Within three months of exposure to different land-use treatments in the small area of the common garden, surrounded by the same environment, microbial communities clearly diverged to treatment-specific compositions.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Relocation as a strategy to avoid environmental changes might often fail because of time constraints, continued habitat shrinking, or a lacking spatial connectivity within a species’ range of dispersal (Asamoah et al, 2021; Corlett & Westcott, 2013; Gómez-Ruiz & Lacher Jr, 2019; Renton et al, 2013); likewise, the process of evolutionary adaptation to rapid alterations also takes several generations and might be too slow in most cases (Etterson & Shaw, 2001). Our data experimentally support recent findings that land-use not only affects plants and plant communities, but also the diversity and composition of plant-associated bacterial and fungal communities (Bai et al, 2023; Estendorfer et al, 2017; Gaube et al, 2021). Our data additionally demonstrate the pace and small scale of such alterations: Within three months of exposure to different land-use treatments in the small area of the common garden, surrounded by the same environment, microbial communities clearly diverged to treatment-specific compositions.…”
Section: Discussionsupporting
confidence: 91%
“…Natural modulations of plant-associated microbial communities in response to environmental stresses can represent an alternative – and faster – way for plants to cope with alterations in land-use and other components of global change (Afkhami, 2023; Allsup et al, 2023; Lau & Lennon, 2012; Trivedi et al, 2022). In fact, ecological and evolutionary microbiome responses can easily keep pace with environmental changes (Martiny et al, 2023) and land-use history, intensity, and agricultural practices have been shown to affect the diversity and composition of bacterial and fungal communities in the soil or associated with plants (Abrahao et al, 2022; Bai et al, 2023; Estendorfer et al, 2017; Gaube et al, 2021; Li et al, 2019). These rapid responses of plant-associated microbiomes may then, in turn, have positive effects on plant phenotype and performance, increasing plant species’ tolerance to changes (Friesen et al, 2011; Jiang et al, 2023).…”
Section: Introductionmentioning
confidence: 99%